SHIFTING MEANING OF THE HIJRAH HADITH IN ECONOMIC CONSIDERATION ON SOCIAL MEDIA - Garwan, Muhammad Sakti (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2020)
Hijrah is a term that has been trending in recent years in Indonesia. The term’s popularity is due to the rise of reporting on the hijrah movements carried out by public figures. This trend then impacts the development of the fashion industry to produce the needs of those who do hijrah. The production that is done eventually requires advertising, so some people use it as a goal in doing hijrah. In this context, this study aims to find a shift in the understanding of hijrah, from religious reality to economic reality. To achieve this purpose, this study uses qualitative methods with library research techniques. As part of data analysis, this study uses framing analysis. This study concludes a shift in the meaning of hijrah from a religious base to a change in soacial identity. The change in social identity, in this context, then continues to the alteration of religious narratives as economic commodities. The behavior displayed by some people who do hijrah becomes blurred. The intention to do hijrah does not always initiate from self-improvement efforts by leaving bad behavior towards good behavior but can be preceded by economic goals. Hijrah can be encouraged to meet the advertising needs of products that have been issued by the clothing industry. This affects the vulnerability of religious communities in Indonesia.